Global Transcriptome and Coexpression Network Analyses Reveal New Insights Into Somatic Embryogenesis in Hybrid Sweetgum (Liquidambar styraciflua × Liquidambar formosana) - Qi, Shuaizheng; Zhao, Ruirui; Yan, Jichen; Fan, Yingming; Huang, Chao; Li, Hongxuan; Chen, Siyuan; Zhang, Ting; Kong, Lisheng; Zhao, Jian; Zhang, Jinfeng (Frontiers in Plant Science, 2021)
Somatic embryogenesis (SE) is a multi-step regeneration process that includes three stages, namely, embryogenic induction, embryonic development, and somatic embryo development. Hybrid sweetgum SE has been established; however, the mechanism of SE remains unclear. In the present study, we analysed the transcriptome profiles and gene expression regulation changes via RNA sequencing from three distinct developmental stages of hybrid sweetgum: non-embryogenic callus, embryogenic callus (EC), and redifferentiation. Comparative transcriptome analysis showed that 19,957 genes were differentially expressed in seven pairwise comparisons of SE. Among these, plant hormone signalling-related genes, especially the auxin and cytokinin signalling components, were significantly enriched. The K-means method was used to identify multiple transcription factors, including HB-WOX, B3-ARF, AP2/ERF, and GRFs (growth regulating factors). These transcription factors showed distinct stage- or tissue-specific expression patterns mirroring each of the 12 superclusters to which they belonged. For example, BBM1, WOX9, and WOX11, with potential roles in embryogenic competence, were among the EC-specific transcription factors. GRF and LEAs were involved in specific somatic embryo development stages. A weighted gene co-expression network analysis (WGCNA) was used in conjunction with the gene expression profiles to recognize the genes and modules that may associate with specific tissues and stages. We constructed co-expression networks and revealed 22 gene modules. Four of these modules with properties relating to embryonic potential, early somatic embryogenesis, and somatic embryo development, as well as some hub genes, were identified for further functional studied. Through a combination analysis of WGCNA and K-means, somatic embryo-related genes including AUX22, ABI3, ARF3, ARF5, AIL1, AIL5, AGL15, WOX11, WOX9, IAA29, BBM1, MYB36, LEA6, SMR4 and others were obtained, indicating that these genes play an important role in the morphogenesis of somatic embryos. These results provide new insights into the molecular mechanisms of SE and suggest strategies that could be used for regulating its developmental processes.